2019
DOI: 10.3389/fnhum.2019.00273
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Transcranial Direct Current Stimulation for Cognitive Rehabilitation in Patients With Mild or Major Neurocognitive Disorders: A Randomized Sham-Controlled Pilot Study

Abstract: IntroductionTranscranial direct current stimulation (tDCS) is a potentially novel strategy for cognitive enhancement in patients with mild or major neurocognitive disorders. This study aims to assess the safety and efficacy of tDCS during cognitive training on cognitive functioning in patients with mild or major neurocognitive disorders.MethodsThis study was primarily a single arm for safety, secondary a two-arm, parallel, randomized, and sham-controlled trial for potential efficacy. Patients with mild or majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Second, the long-term cognitive benefits of tDCS cannot be assessed. Our pilot study 16 indicated the short-term effects of tDCS on cognition in 10 sessions. Because the long-term cognitive effects of tDCS are uncertain, no large-scale trials have assessed these effects.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Second, the long-term cognitive benefits of tDCS cannot be assessed. Our pilot study 16 indicated the short-term effects of tDCS on cognition in 10 sessions. Because the long-term cognitive effects of tDCS are uncertain, no large-scale trials have assessed these effects.…”
Section: Discussionmentioning
confidence: 82%
“…The advantage of this study is its appropriate sample size calculation for global cognition based on our previous pilot study 16 when compared with most other previous studies that lacked proper sample size calculations. Trial adherence strategies include reducing the number of hospital visits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations